2008
DOI: 10.1016/j.brat.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Time course of selective attention in clinically depressed young adults: An eye tracking study

Abstract: Depressed individuals display biased attention for emotional information when stimuli are presented for relatively "long" (e.g., 1 second) durations. The current study examined whether attentional biases are sustained over a much longer period. Specifically, clinically depressed and never depressed young adults simultaneously viewed images from four emotion categories (sad, threat, positive, neutral) for 30 seconds while line of visual gaze was assessed. Depressed individuals spent significantly more time view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
229
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(260 citation statements)
references
References 23 publications
26
229
4
1
Order By: Relevance
“…For this study, the total fixation frequency (i.e., total number of fixations) and total fixation duration (i.e., summation of the duration across fixations) on the target words in the scrambled sentences (i.e., the areas of interest) served as the key dependent variables. These parameters are commonly reported indices of attention bias sensitive to individual differences related to depression (e.g., Kellough, Beevers, Ellis, & Wells, 2008;Leyman, De Raedt, Vaeyens, & Philippaerts, 2011) and are assumed to reflect different mechanisms of attention (see Armstrong & Olatunji, 2012). More specifically, the ATTENTION, INTERPRETATION, AND MEMORY BIASES 11 fixation frequency parameter indexes (re)orienting of attention (cf.…”
Section: Assessment Of Cognitive Biasesmentioning
confidence: 99%
“…For this study, the total fixation frequency (i.e., total number of fixations) and total fixation duration (i.e., summation of the duration across fixations) on the target words in the scrambled sentences (i.e., the areas of interest) served as the key dependent variables. These parameters are commonly reported indices of attention bias sensitive to individual differences related to depression (e.g., Kellough, Beevers, Ellis, & Wells, 2008;Leyman, De Raedt, Vaeyens, & Philippaerts, 2011) and are assumed to reflect different mechanisms of attention (see Armstrong & Olatunji, 2012). More specifically, the ATTENTION, INTERPRETATION, AND MEMORY BIASES 11 fixation frequency parameter indexes (re)orienting of attention (cf.…”
Section: Assessment Of Cognitive Biasesmentioning
confidence: 99%
“…Two of the above-cited studies also found that depressed individuals paid more attention to sad stimuli relative to healthy controls (Eizenman et al, 2003;Kellough et al, 2008). However, no study found differences in the eye-gaze patterns related to threatening stimuli between depressed and non-depressed individuals (Armstrong and Olatunji, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…Of particular relevance here is the free-viewing task, in which participants are required to focus on a central fixation point, and then asked to scan/re-scan several stimuli (2-4 stimuli, e.g., images, faces, or words) presented simultaneously, depicting differing valences (happy, sad, threat or neutral) for around 10-30 s. A number of studies assessed the maintenance of attention over the entire trial (e.g., by measuring the total fixation time on each image; see Eizenman et al, 2003;Kellough et al, 2008;Leyman et al, 2011;Sears et al, 2010Sears et al, , 2011Ellis et al, 2011). Depressed individuals attended less to happy stimuli than nondepressed individuals (i.e., an "anhedonic bias" was found; Kellough et al, 2008;Leyman et al, 2011;Sears et al, 2010Sears et al, , 2011Ellis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations